Synthesizing and Using Iron Oxide Nanoparticles as Nanocomposite in Cotton Fabrics Nanofinishing - Hoda Sharouf; Ziad Saffour (مجلة بغداد للعلوم)
Metal oxide nanoparticles, including iron oxide, are highly considered as one of the most important species of nanomaterials in a varied range of applications due to their optical, magnetic, and electrical properties. Iron oxides are common compounds, extensive in nature, and easily synthesized in the laboratory. In this paper, iron oxide nanoparticles were prepared by co-precipitation of (Fe+2) and (Fe+3) ions, using iron (II and III) sulfate as precursor material and NH4OH solution as solvent at 90°C. After the synthesis of iron oxide particles, it was characterized using X-ray diffraction (XRD), infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). These tests confirmed the obtaining of iron oxide nanoparticles with a crystalline structure in the form of (spinel), and the size of nanoparticles ranging from 13-24 nm.